Criminal Prosecution for Forest Arson under the Forest and Woodland Law "A Comparative Study" - Shakir Khairallah, Researcher. Mohammed; Fadhil Rekab, Prof.Dr. Emad (Basra studies journal, 2025)
The This research sheds light on the penal mechanisms employed by Iraqi law and comparative legal systems to confront forest fire crimes, whether these incidents occur deliberately by the perpetrator or as a result of negligence. Forest fires pose a major threat to various living organisms, especially humans، as they cause significant damage to food security and sustainable development—effects that may persist for future generations—along with the difficulty of rehabilitating soil damaged by fire. The study aims to identify gaps in the penal mechanisms used to address forest fires and to propose appropriate solutions. It is divided into two sections: the first section examines the crime of intentionally setting a forest fire, while the second addresses the crime of causing a forest fire through negligence.